1994
DOI: 10.1200/jco.1994.12.5.981
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of primary lung cancer in patients less than 40 years of age.

Abstract: Although younger patients tended to have more advanced disease, long-term survival in these patients did not differ from that of older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
4
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 6 publications
4
32
4
2
Order By: Relevance
“…8,30) Previous studies have reported that fewer young patients present with early-stage disease. 3,6,8,9,13,[15][16][17] However, our study revealed that 31.1% of lung cancer patients younger than 50 years presented with local-stage disease, and a similar percentage of older patients presented with the same stage. As a whole, there was no significant difference between the younger and older patient groups in the stage at which patients presented.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…8,30) Previous studies have reported that fewer young patients present with early-stage disease. 3,6,8,9,13,[15][16][17] However, our study revealed that 31.1% of lung cancer patients younger than 50 years presented with local-stage disease, and a similar percentage of older patients presented with the same stage. As a whole, there was no significant difference between the younger and older patient groups in the stage at which patients presented.…”
Section: Discussioncontrasting
confidence: 48%
“…3-5, 10, 11, 15, 16) Table V, which includes only data from studies involving satisfactory numbers of subjects and/or that were statistically managed, shows that results of these studies have been biased by differences in the databases used and that some studies only evaluated patients who underwent surgical resection. 10,15,16) Moreover, the definition of young patients differed, with some investigators using 40 years and others using 50 years as the cut-off age. Therefore, these results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, higher rates of adenocarcinoma have been reported in young patients and in female patients. [2,23] Some authors have reported comparable prognoses and survival rates between young and advanced age patients, [22,23] while others indicated either unfavorable [24,25] or better [8,14] prognoses and survival rates for older patients. In our study of patients aged ≤55 years and >55 years, the most frequently seen histopathological type was squamous cell carcinoma and no significant difference was found between groups in disease stage; clinical, demographic, surgical, or oncological treatment characteristics; or overall survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Numerous studies have been performed with lung cancer patients of various age groups. [6][7][8] Therefore, there are conflicting results concerning histopathological types, survival rates, and treatment characteristics with regard to young patients. [9][10][11] This study was designed to examine sociodemographic, clinical, radiological, histopathological, and survival characteristics of patients with the diagnosis of lung cancer aged ≤55 and >55 years.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our data (Table 2), it has been reported that younger patients with lung cancer typically present with an advanced stage, and have relatively short survival times (5-7). Some investi- gators have suggested that the lower occurrence of early-stage disease in younger patients may be due to an intrinsically more aggressive disease (8,9), whereas others have attributed it to the delayed diagnosis that results from a low degree of suspicion of cancer in younger patients (3,4,10). Recently, Ramalingamet al have reported that lung cancer is not an aggressive disease in younger patients, all patients should be treated according to the same therapeutic guideline (2).…”
Section: Discussionmentioning
confidence: 99%